2011
DOI: 10.1523/jneurosci.5346-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Subcortical Spreading Depression in Familial Hemiplegic Migraine Type 1 Mutant Mice

Abstract: Familial hemiplegic migraine type 1, a monogenic migraine variant with aura, is linked to gain-of-function mutations in the CACNA1A gene encoding CaV2.1 channels. The S218L mutation causes severe channel dysfunction, and paroxysmal migraine attacks can be accompanied by seizures, coma, and hemiplegia; patients expressing the R192Q mutation exhibit hemiplegia only. Familial hemiplegic migraine knock-in mice expressing the S218L or R192Q mutation are highly susceptible to cortical spreading depression, the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
101
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 49 publications
11
101
1
Order By: Relevance
“…A previous report found that SD is constrained to the cortex in WT mice but can invade the striatum in R192Q mice and can invade the striatum, hippocampus, and, occasionally, thalamus in S218L mice (28). Our data generally are in line with these findings, except that we did not observe SD invasion of the thalamus in S218L animals (Figs.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…A previous report found that SD is constrained to the cortex in WT mice but can invade the striatum in R192Q mice and can invade the striatum, hippocampus, and, occasionally, thalamus in S218L mice (28). Our data generally are in line with these findings, except that we did not observe SD invasion of the thalamus in S218L animals (Figs.…”
Section: Resultssupporting
confidence: 92%
“…Because WT animals did not display subcortical SD in vivo, it is likely that, like the hippocampus, the striatum is capable of SD but cannot normally propagate the wave in response to adjacent cortical SD. It has been suggested that in FHM-1 mice SD may spread to the striatum and hippocampus via the amygdala and subiculum, respectively, and that lower neuronal densities in these areas may be responsible for limiting SD spread in WT animals (28). Our data from R192Q animals support this view with respect to the anatomical entry point of SD into these structures for this strain.…”
Section: Sd Spreads To Subcortical Structures In Both Fhm-1 Strains Bsupporting
confidence: 77%
See 2 more Smart Citations
“…SD and calcium homeostasis have been extensively studied in voltage-gated P/Q-type Ca 2+ channel mutations, where a gain-of-function results in a several-fold decrease in cortical SD threshold. The degree of facilitation of the SD phenotype in RQ mutants detected here is somewhat smaller than that found in one of the PQ channel mutants, R192Q, where SD propagation was greatly enhanced and SD propagated into subcortical structures (38). These mutant mice also had spontaneous seizures and shorter survival than the RQ mutant mice studied here.…”
Section: Variable Severity Of Calcium Homeostasis Phenotype In Mouse contrasting
confidence: 67%